Impact of midgut microbiota with Bt toxin to enhance the insecticidal activity against Spodoptera litura (Fab.) (Lepidoptera: Noctuidae) - A. Kavitha,; Alaguundaram P,; Asha Raja A,; Mahesh R,; Baburajan R, (The Bioscan, 2024)
Biological pest control and management using the gutbiota species is recently considered to be a safe and cost-effective strategy. This study investigates the effect of gut biota in combination with Bt-toxin in inducing mortality among the pest host Tobacco caterpillar (Spodoptera litura). Egg mass of S. litura were collected and larvae were maintained in lab conditions. Bacillus thuringiensis (Bt) was cultured from soil sample and the Bt-toxin Cry1, Cry2 were confirmed by PCR and extracted by centrifugal method. DNA was extracted from the larval midgut microbiota, and Sanger sequencing was performed for candidate 16SrRNA regions. Mortality of S. litura larvae treated with formulations of Bt-Toxin combined with E.mundtii, E. gallinarum, Acinetobacter sp, Bacillus sp, E. cloacae, E. coli, and P. aeruginosa were analyzed. Highest mortality of 72% and 60% were observed with Bt-Toxin + E. cloacae and Bt-Toxin +Bacillus sp combinations, respectively. In addition, One-way ANOVA analysis indicated significant (p  0.001) difference among the mortality across the combination groups (F [7,392] = 16.539). Hence this present study contemplates the possibility of utilizing E.cloacae as a preferable biocontrol agent for effective downstream pest control and management.